Costos laborales, economia informal y reformas a la legistacion laboral en Bolivia - Soraya Román (Institute for Advanced Development Studies (INESAD), 2011)
– Develops and sets a general equilibrium dynamic and stochastic model with 2 sectors, formal and informal, for the economy in Bolivia. The goal of the model is to evaluate the impact of recent labor market reforms on employment, wages and the product. Specifically, analyzes the effect of a tax increase in employment which serves for the creation of a semi - contributory fund with a redistributive character that is defined in the New Pension Law. On the other hand, analyzes the effect of an increase in firing and hiring costs, defined in the draft Labor Code. The results indicate that in the first case, the reform increases the informality, which causes decrease in the long term variations of the number of contributors to the new background, affecting its sustainability. In the second case, the reform reduces the mobility of formal and informal employment within each sector and across sectors. This increases the time required for product recovery in case of a recession or respond in case of an expansion.
Keywords: E26; E32; J32; J38; 330; Labor economy; Informality; Adjustment costs; Evaluation of labor market reforms; DSGE.; Informeller Sektor; Arbeitskosten; Arbeitsrecht; Dynamisches Gleichgewicht; Bolivien